Looking beyond the screen: A systematic review of safety in control rooms - Raziyeh Janizadeh; Alireza Choobineh; Soheyla Ahmadi Charkhabi; Mehdi Jahangiri (Heliyon, 2024)
As a complex socio-technical system, the Control Room (CR) is central to many industries, such as process, aviation, transportation, and mining. CRs' complexity impacts the safety, operational, engineering, regulatory, and financial performance of the system. In this study, a search strategy was defined and applied to three reputable databases: Scopus, Web of Science, and PubMed. The search results underwent a two-stage screening process based on inclusion and exclusion criteria. The inclusion criteria were investigating the safety in the CR, full-text availability, and writing in English. The exclusion criteria were unrelated to the safety in the CR, non-English Language, and non-original studies. A total of 59 studies were included in the analysis. The included articles were systematically reviewed from the Human Reliability Assessment (HRA) and Human Factors Engineering (HFE) perspectives. Since these records covered various subjects related to human reliability and human factor aspects, a categorization step was added to the study process. In this step, all included studies were categorized based on their subjects. A total of 7 categories were identified, including reliability (17 documents), safety performance (13 documents), decision-support systems (7 documents), fire safety (2 documents), communication/teamwork (11 documents), situation awareness (4 documents), and others (5 documents). Finally, the included studies in each category were analyzed and discussed. The results of this study help identify different aspects of safety in the control room and plan to improve their safety weaknesses, which ultimately leads to an increase in the efficiency of employees and various industries.